2009
DOI: 10.1063/1.3131628
|View full text |Cite
|
Sign up to set email alerts
|

Ion spectrometer composed of time-of-flight and Thomson parabola spectrometers for simultaneous characterization of laser-driven ions

Abstract: An ion spectrometer, composed of a time-of-flight spectrometer (TOFS) and a Thomson parabola spectrometer (TPS), has been developed to measure energy spectra and to analyze species of laser-driven ions. Two spectrometers can be operated simultaneously, thereby facilitate to compare the independently measured data and to combine advantages of each spectrometer. Real-time and shot-to-shot characterizations have been possible with the TOFS, and species of ions can be analyzed with the TPS. The two spectrometers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In the described experimental campaign, the advanced TOF method allowed to obtain calibrated spectra of protons up to ~ 2.5 MeV with very high accuracy, much better than that typically obtained with Thomson spectrometers 38,59 . It is worth to notice that the approaches here followed for estimating the range where the detected signal is assumed to be purely due to protons-based in one case on established theoretical considerations [2][3][4]41 and in the other case on the use of a suitable filter-results to be rather conservative, if compared with the energy spectra given in reference 60 . In that case data obtained by Thomson spectrometers, employed in experimental campaigns at very similar regimes to that described in the present paper, showed that the energy of carbon ions was significantly lower than the minimum proton energy considered in the present analysis 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the described experimental campaign, the advanced TOF method allowed to obtain calibrated spectra of protons up to ~ 2.5 MeV with very high accuracy, much better than that typically obtained with Thomson spectrometers 38,59 . It is worth to notice that the approaches here followed for estimating the range where the detected signal is assumed to be purely due to protons-based in one case on established theoretical considerations [2][3][4]41 and in the other case on the use of a suitable filter-results to be rather conservative, if compared with the energy spectra given in reference 60 . In that case data obtained by Thomson spectrometers, employed in experimental campaigns at very similar regimes to that described in the present paper, showed that the energy of carbon ions was significantly lower than the minimum proton energy considered in the present analysis 60 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to notice that the approaches here followed for estimating the range where the detected signal is assumed to be purely due to protons-based in one case on established theoretical considerations [2][3][4]41 and in the other case on the use of a suitable filter-results to be rather conservative, if compared with the energy spectra given in reference 60 . In that case data obtained by Thomson spectrometers, employed in experimental campaigns at very similar regimes to that described in the present paper, showed that the energy of carbon ions was significantly lower than the minimum proton energy considered in the present analysis 60 . Hence, for future development of the technique discussed here, its simultaneous employment together with a Thomson spectrometer, placed at similar detection angle, will be fruitful for extending the effective energy range where a pure proton spectrum is retrievable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a platform for developing diagnostics for OMEGA-EP 22 and damage testing of optics, the MTW is being used for studies of LPI in the context of backlighter development and basic science. A Thomson parabola ion spectrometer (TPIS), [23][24][25][26][27] previously designed, constructed and implemented on the MTW, was used for measurements of charged particle energy spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Even when such ultra-short pulses of protons are spread out over a flight path of 1-2 m due to different particle momenta, they will most likely produce an overlap signal inside a scintillator. Nevertheless, this type of detectors has been successfully applied for the measurement of energy spectra of laser-accelerated protons [10], [11]. Our design, as motivated in section II, tends to offer maximum flexibility to obtain the proton spectral distribution, especially at the high-energy limit, over a wide range of particle numbers.…”
Section: Online Monitormentioning
confidence: 99%
“…The detection time after the laser pulse is directly related to the proton energy (time-offlight method, TOF) [11], [17]. In our case, the projected range of kinetic energies (0.5-15 MeV) corresponds to flight times between 153 and 30 ns at 1.5 m target distance, respectively.…”
Section: Design Considerationsmentioning
confidence: 99%